Hepatic Nervous System in Development, Regeneration, and Disease. Issue 6 (15th August 2021) - Miller, Bess M.; Oderberg, Isaac M.; Goessling, Wolfram
Abstract : The liver is innervated by autonomic and sensory fibers of the sympathetic and parasympathetic nervous systems that regulate liver function, regeneration, and disease. Although the importance of the hepatic nervous system in maintaining and restoring liver homeostasis is increasingly appreciated, much remains unknown about the specific mechanisms by which hepatic nerves both influence and are influenced by liver diseases. While recent work has begun to illuminate the developmental mechanisms underlying recruitment of nerves to the liver, evolutionary differences contributing to species‐specific patterns of hepatic innervation remain elusive. In this review, we summarize current knowledge on the development of the hepatic nervous system and its role in liver regeneration and disease. We also highlight areas in which further investigation would greatly enhance our understanding of the evolution and function of liver innervation.